2022
DOI: 10.1037/aap0000234
|View full text |Cite
|
Sign up to set email alerts
|

“Please forgive me:” Asian and Pacific Islander Americans’ suicide notes.

Abstract: Suicide notes are an understudied, yet important area of research because they provide insights into what suicide decedents intend to communicate to others in the moments before their tragic death. In this article, the authors report the first known national study to focus exclusively on Asian and Pacific Islander Americans' (APIAs) suicide notes using data from the National Violent Death Reporting System (N = 3,657). About 31% of APIA decedents left suicide notes. Females and youths (below 25 years old) had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…There are several potential reasons for this. First, previous studies on suicide among Asian American adults suggest that perceived burdensomeness may be particularly salient in precipitating suicide ideation in this group as it may be accompanied by shame ( Wong et al, 2022 ). For some Asian individuals, perceiving that they have brought shame to their close friends, family, and their communities may amplify their feelings of being a burden to their loved ones and society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several potential reasons for this. First, previous studies on suicide among Asian American adults suggest that perceived burdensomeness may be particularly salient in precipitating suicide ideation in this group as it may be accompanied by shame ( Wong et al, 2022 ). For some Asian individuals, perceiving that they have brought shame to their close friends, family, and their communities may amplify their feelings of being a burden to their loved ones and society.…”
Section: Discussionmentioning
confidence: 99%
“…For some Asian individuals, perceiving that they have brought shame to their close friends, family, and their communities may amplify their feelings of being a burden to their loved ones and society. In fact, Wong et al (2022) found that among suicide notes left by Asian decedents (from National Violent Death Reporting System), messages asking for forgiveness were commonly observed suggesting that absolving feelings of perceived burdensomeness may have been the main motivator for suicide. Additionally, Tang and Masicampo (2018) found that perceived burdensomeness increased Asian American college students’ suicide ideation and decreased their willingness to seek help.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this experience was unique to Black Americans may limit their ability to pull together, as other racial/ethnic minority groups as well as White Americans might have struggled to empathize and build meaningful community. Related constructs of social isolation, thwarted belongingness and trauma impart suicide risk (Polanco-Roman et al, 2021;Van Orden et al, 2010;Wong et al, 2022). Thus, future research should examine if the findings from Curtis et al (2021) extend to other communities of color, and how such findings transmit to risk for suicide.…”
Section: Pulling Togethermentioning
confidence: 99%
“…Similarly, the literature indicates that among AAPI Americans, facing school-based or general interpersonal violence is related to increased risk for suicide-related thoughts and behaviors (Leung & Lai, 2023). In a qualitative analysis of 2003-2017 data from the National Violent Death Reporting System (NVDRS), thwarted belongingness was a common difficulty reported by AAPI suicide decedents (Wong et al, 2022). More general research on the relationship between racial/ethnic discrimination and suicide risk has found that such relations may be mediated by posttraumatic symptoms such as stress sensitivity and dissociative symptoms (Polanco-Roman et al, 2021); thus, racially-motivated violence in 2020 may have had traumalike impacts on the mental health of people of color.…”
Section: Racially-motivated Victimization and Embracing Lifementioning
confidence: 99%